A Note on Lichens on Shorea robusta in a Biosphere Reserve, Central India - Shukla, Achuta N.; Singh, K. P. (Indian Forester, 2011)
The paper enumerates 45 species of 13 genera of the lichens growing on Shorea robusta Gaertn. f ., trees of Achanakmar-Amarkantak Biosphere Reserve, Madhya Pradesh and Chhattisgarh, mostly the foliose forms of lichens show their predominance as the Parmotrema, Dirinaria, Pertusaria spp. were growing very commonly on young as well as older bark, on breast height.